A Pilot of an Intervention Delivered to Chinese- and Spanish-Speaking Carers of People With Dementia in Australia. (February 2014) - Leone, Desiree; Carragher, Natacha; Santalucia, Yvonne; Draper, Brian; Thompson, Larry W.; Shanley, Christopher; Mollina, Angelica; Chen, Langduo; Kyriazopoulos, Helena; Thompson, Dolores Gallagher
There are limited language- and culture-specific support programs for carers of people with dementia living in Australia. A group intervention for use with Chinese and Spanish speakers in the United States was adapted to the Australian context, and a pilot study was undertaken with these 2 communities. The intervention is based on a cognitive behavioral therapy approach and was delivered by bilingual health professionals. The adapted material comprised 7 sessions, spanning 2 hours in duration. All 22 participants completed the Depression Anxiety and Stress Scale—Short form (DASS-21) pre- and postintervention. A significant decrease in depression, anxiety, and stress was observed among Spanish speakers; a significant decrease in depression and anxiety was present among the Chinese speakers. The implications are considered in the context of Australia's changing aged care service system.